INCIDENCE OF INJURIES IN SOCCER PLAYERS – MAPPINGFOOT: A PROSPECTIVE COHORT STUDY - Drummond,Felix Albuquerque (2021)
ABSTRACT Introduction: Although the positive effects of physical activity on global health are well documented, sports practice is associated with a greater risk of injury; in professional soccer in particular, the risk is substantial. Objective: The primary objective of this study was to investigate the incidence of injuries among male athletes competing in the regional soccer championship. The secondary objective was to determine the prevalence of injuries. Methods: In this prospective cohort study, level of evidence II, the incidence and prevalence of injuries were assessed using an adapted version of the UEFA Champions League Study questionnaire. Results: This study included 310 male athletes from ten teams, aged 26.53±4.75 years, height 180.93±6.49 cm, and weight 79.32±8.29 kg, with a 4-month follow-up. Ninety-two injuries were recorded, representing a prevalence of 29.68% injuries. The body part most frequently injured was the lower limbs (86.9%). The main types of injuries were muscle tear/strain (37.0%), sprain/ligament (19.6%), and other injuries (14.1%). The injuries were mainly caused during run/sprint (33.7%), kick (12.0%) and jumping/landing (6.5%). The incidences of injuries were 15.88±8.57, 2.04±1.09, and 3.65±1.50 injuries/1000h of exposure during matches, training, and matches/training, respectively. Time-loss over the season was between 1 and 50 days, and the severity of the injuries was as follows: light (25%), minor (22.8%), moderate (43.5%) and severe (8.7%). Conclusion: This study suggests that there is a higher incidence of injuries during matches compared to training, among male regional soccer championship players. The lower limbs are the body part most affected, with a higher prevalence of rupture/strain in the thigh region, during running/sprinting. Level of evidence II; Prospective Cohort Study .